ADVANTAGES OF LEARNING FOREIGN LANGUAGES BY INTERACTIVE METHODS IN CLASSES - Fotima Pirnazarovna, Davronova; Mekhruzkhon Bakhtiyorvich, Bakhtiyorov; Muhammadrizo Safarovich, Karimov; Khojiakbar Tokhirovich, Khabibullayev; Gulmira Abdulloyevna, Nasriyeva; Gulmira Akramovna, Bagirova; Zaynab Isroilovna, Jalilova; Gulzifa Azimovna, Imomova (Journal of Higher Education and Academic Advancement, 2025)
Objective: This paper aims to examine the advantages of using interactive methods in foreign language learning, particularly English, and their effectiveness in comparison to traditional teaching approaches. Method: A qualitative analysis was conducted to explore the impact of interactive teaching methods on language acquisition, including case studies and examples of practical application in the classroom. The study involved observations of language instructors and feedback from students engaged in interactive learning activities. Results: The findings demonstrate that interactive methods enhance students' engagement, accelerate language learning, and promote retention of knowledge. Students showed greater enthusiasm and improved performance when involved in interactive, learner-centered activities. Moreover, teachers reported greater satisfaction in observing the active participation and creativity of their students. Novelty: The study introduces a critical perspective on the transition from traditional teaching methods to more innovative, interactive approaches. It highlights the positive effects of these methods not only on language acquisition but also on fostering a more dynamic and engaging learning environment, suggesting that interactive learning is essential for the future of foreign language education.